2023
DOI: 10.1186/s12903-023-02774-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three-dimensional maxillary growth across spheno-occipital synchondrosis maturation stages

Abstract: Background This study aimed to three-dimensionally compare the maxillary growth among the spheno-occipital synchondrosis (SOS) maturation stages in both genders. Methods This is a cross-sectional study of a retrospective type in which cone-beam computed tomography (CBCT) images of 500 patients aged 6 to 25 years (226 males and 274 females) were analyzed. The SOS was evaluated using the four-stage scoring system; completely open, partially fused, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
2
1
Order By: Relevance
“…In our study, we found that the RGR of maxillary length decreased in girls since SOS 4, whereas boys exhibited relatively stable growth until SOS 4, followed by significant deceleration starting from SOS 5. Al‐Gumaei et al 28 also analysed the relationship between SOS fusion and maxillary growth, suggesting that maxillary growth during the fusing SOS stage was more significant than during the open or fused status, showing a growth peak during the fusing period, partially different from our findings. However, it is worth noting that their study was cross‐sectional, and they directly compared growth increments between subsequent stages, disregarding the influence of the time span on the magnitude of growth, which may significantly affect result comparability.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In our study, we found that the RGR of maxillary length decreased in girls since SOS 4, whereas boys exhibited relatively stable growth until SOS 4, followed by significant deceleration starting from SOS 5. Al‐Gumaei et al 28 also analysed the relationship between SOS fusion and maxillary growth, suggesting that maxillary growth during the fusing SOS stage was more significant than during the open or fused status, showing a growth peak during the fusing period, partially different from our findings. However, it is worth noting that their study was cross‐sectional, and they directly compared growth increments between subsequent stages, disregarding the influence of the time span on the magnitude of growth, which may significantly affect result comparability.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the extended duration of fusing status made it challenging to pinpoint the growth peak accurately. Additionally, the cross‐sectional study conducted by Al‐Gumaei et al 28,29 compared SOS fusion stages with the maxillomandibular growth in three dimensions. However, it still suffered from the limitation of a wide span of SOS fusion stages, which made it difficult to precisely gauge growth dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation